EFECTIVIDAD DEL FENBENDAZOL Y PRAZIQUANTEL PARA EL CONTROL EN DOSIS ÚNICA DE NEMÁTODES Y CÉSTODES EN PERROS - Cárdenas R., Manuel (2006)
The objective of the study was to evaluate the therapeutic effectiveness of thefenbendazole-praziquantel combination against nematode and cestode parasitismin dogs. A single dose of 100 mg of fenbendazole and 5 mg of praziquantel perkilogram of body weight was orally administered. Ten female/male 12-14 weeks oldpupies were naturally infected with Toxocara canis and Dipylidium caninum, anddivided in a control and treated groups. Adult forms of the parasites were searchedin the necropsy at day 4 after treatment. The effectiveness was 92.5 and 100%against T. canis and D. caninum, respectively, and without side effects in treatedanimals. The results showed that the fenbendazole-praziquantel combination at thespecified dose was highly effective against these parasites.